Alih dan Campur Kode dalam Interaksi Jual Beli di Pasar Kayen Kabupaten Pati: Kajian Sosiolinguistik - Vera Wahyu Wulandari; Sri Suciati; Pipit Mugi Handayani (Universitas PGRI Semarang, 2023)
The purpose of this study is to describe the form of code switching and code mixing in buying and selling interactions and to describe the factors that cause code switching and code mixing in interactions between sellers and buyers at Kayen Market, Pati Regency: Sociolinguistic Studies. The theory used is a qualitative descriptive approach. Sources of data in this study are sellers and buyers in Kayen Market by using the concept of speech as an approach. The data in this study is the transcription of the dialogue between sellers and buyers in Kayen Market. The data collection technique used in this research is the technique of recording, listening and taking notes. The results of the analysis from the study of Code Switching and Mixing in Buying and Selling Interactions at Kayen Market, Pati Regency: Sociolinguistic Studies, it can be concluded that the code switching that occurs in Kayen Market is internal code switching between languages, namely Indonesian to regional languages or Javanese languages, as well as events Code mixing that occurs in Kayen Market, there is internal code mixing, namely the insertion of words and phrases. The form of code switching and mixing is in the form of language switching from Javanese to Indonesian and vice versa.ABSTRAKTujuan dari penelitian adalah mendeskripsikan wujud alih kode dan campur kode dalam interaksi jual beli dan mendeskripsikan faktor yang penyebabkan terjadinya alih kode dan campur kode dalam interaksi antara penjual dan pembeli di Pasar Kayen Kabupaten Pati: Kajian Sosiolinguistik. Teori yang digunakan pendekatan deskriptifÂ kualitatif. Sumber data dalam penelitian ini adalah penjual dan pembeli di Pasar Kayen dengan menggunakan konsep tutur sebagai ancangan. Data dalam penelitian ini adalah transkripsi dialog antara penjual dan pembeli di Pasar Kayen. Teknik pengumpulan data yang digunakan dalam penelitian ini adalah teknik rekam, simak dan catat. Hasil analisis dari penelitian Alih dan Campur Kode dalam Interaksi Jual Beli di Pasar Kayen Kabupaten Pati: Kajian Sosiolinguistik ini dapat disimpulkan bahwa alih kode yang terjadi di Pasar Kayen adalah alih kode internal antar bahasa yaitu bahasa Indonesia ke bahasa daerah atau bahasa jawa, demikian juga peristiwa campur kode yang terjadi di Pasar Kayen, terdapat campur kode internal yaitu penyisipan kata dan frasa. Bentuk alih dan campur kode berupa peralihan bahasa dari bahasa Jawa ke bahasa Indonesia dan sebaliknya.